Place cells in CA1 lack topographical organization of firing locations - Torstein Slettmoen; Nienke L. de Jong; Hanna Eneqvist; Emilie R. Skytøen; Weijian Zong; May-Britt Moser; Edvard I. Moser (Proceedings of the National Academy of Sciences, 2026)
Topography is a well-described and well-known concept for cortical organization in primary sensory and motor cortices of mammalian brains. Similar isomorphic mapping of the environment is absent in most higher association areas such as the hippocampus; however, some studies have suggested that in hippocampal regions spatially tuned cells may be organized in small anatomical clusters with similar firing field locations. Here, we take advantage of the high spatial resolution provided by two-photon calcium imaging to probe the extent of local functional clustering of hippocampal place cells in freely moving mice. Almost one thousand highly packed CA1 neurons were recorded simultaneously per mouse while they foraged freely in open arenas. Among pairs of place cells, there was no relation between preferred firing position and anatomical proximity. Firing fields were no more similar for nearest neighbors than distant cell pairs. When place cells remapped between different arenas, there was no tendency for correlations in one environment to be transferred to the other. A similar lack of relationship between function and anatomical position was expressed in CA1 cells with firing fields tuned to local objects in the environment. The findings suggest that the encoding of location in CA1 place cells is likely fully nontopographical.